Description of recent discovery of Anthocharis damone Boisduval, 1836 in Serbia and its distribution in Europe (Lepidoptera: Pieridae) - E. Drndic; D. Radevski; M. Miljevic; M. Duric; M. Popovic (SHILAP, 2017)
Anthocharis damone Boisduval, 1836 is known from southern Italy, Greece, Republic of Macedonia, Albania and further in the Middle East. At the end of May and beginning of June 2015 it was recorded for the first time in Serbia. A single isolated colony was found 170 km NW from the northernmost known locality in Europe. This record made us review A. damone distribution in Europe, suggested its possibly wider range over the Balkans and increased the list of butterflies recorded in Serbia to a total of 200 species.